The Influence Of Digital Competencies And Digital Informal Learning In Enhancing Islamic School Teachers’ Instructional Effectiveness In Southern Pakistan - Kashif Majeed, Muhammad; Badariah Ahmad, Tunku; Bin Shamsuddin, Aizat (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Digital information literacy and digital informal learning are especially fundamental in improving the efficiency of teachers instruction within a context of limited resources such as Islamic secondary schools of Southern Pakistan. This paper examines how digital competencies (ex: information literacy, technology use, and communication) and digital informal learning (e.g.: self-directed learning thru online platforms) make teachers able to deliver engaging lessons, manage classrooms, and encourage student-centered learning. Although interest in digital education is increasing, little research has considered such aspects in rural to Islamic schools. In a quantitative research, 450 teachers of Islam secondary schools and Southern Punjab comprised the purposive sample in which the structured questionnaires were administered and assessed using SPSS v 22, descriptive statistics, correlation and multiple linear regression. Results have shown that increased digital capabilities lead to a strong increase in instructional effectiveness, whereas digital informal learning brings cultural awareness and invention of new practices in teaching. A combination of these factors enhances the delivery of the lesson, student participation, and classroom management. The research suggests considering digital competency training and informal learning materials as part of teacher development companies in order to improve educational performance in the under-resourced Islamic schools.